2023
DOI: 10.3390/vaccines11040871
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Neutralizing Antibodies to B.1 and to BA.5 Variant after Booster Dose of BNT162b2 Vaccine in HIV Patients COVID-Naïve and on Successful Antiretroviral Therapy

Abstract: Live virus neutralization is the gold standard to investigate immunity. This prospective observational study aimed to determine the magnitude of response against the original B.1 lineage and against the BA.5 lineage six months after the third BNT162b2 mRNA vaccine dose in patients with HIV infection on successful antiretroviral treatment and no previous SARS-CoV-2 infection. A total of 100 subjects (M/F 83/17, median age 54 years) were included in the analysis: 95 had plasma HIV RNA <40 copies/mL, the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Measuring antibody responses against severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is essential to quantify individual differences in virus-specific humoral immunity after vaccinations or previous infections. This particularly applies to specific patient cohorts like people living with human immunodeficiency virus (HIV) [1,2]. Indeed, recent studies have demonstrated that higher levels of SARS-CoV-2-specific antibodies (e.g., with distinct neutralizing capabilities and of various immunoglobulin classes) correlate with a reduced risk for reinfections with SARS-CoV-2 Omicron variants [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Measuring antibody responses against severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is essential to quantify individual differences in virus-specific humoral immunity after vaccinations or previous infections. This particularly applies to specific patient cohorts like people living with human immunodeficiency virus (HIV) [1,2]. Indeed, recent studies have demonstrated that higher levels of SARS-CoV-2-specific antibodies (e.g., with distinct neutralizing capabilities and of various immunoglobulin classes) correlate with a reduced risk for reinfections with SARS-CoV-2 Omicron variants [3][4][5].…”
Section: Introductionmentioning
confidence: 99%